Injectable Filler Technique for Face Lifting Based on Dissection of True Facial Ligaments. (10th December 2020) - Cong, Li-Yao; Duan, Jing; Luo, Cheng-En; Luo, Sheng-Kang
Abstract: Background: Strengthening weakened ligament tissues with injectable fillers to improve their supportive effect may achieve the aesthetic goal of face lifting. Objectives: The aim of the study was to design an injectable technique for enhancing the true facial ligaments and dissect the ligaments to provide anatomical guidance for effective injection. Methods: Six true facial ligaments were chosen as target anatomical sites for injection. Specimens were dissected, and 3-dimensional (3D) images were reconstructed to confirm the exact location of each injection site and to confirm that the proposed injection routes will not cause dangerous vascular damage. A total of 5 patients received the injections; 3D images were taken before and after the injections for comparison and clinical outcome assessments. Results: The injection technique was designed to target 6 true facial ligaments, as follows. Site 1 targeted the temporal ligamentous adhesion region to lift the lateral ends of the eyebrows. Site 2 targeted the region of the lateral orbital thickening to lift the lateral canthus. Site 3 and site 4 targeted the zygomatic retaining ligaments and zygomatic cutaneous ligaments, respectively, to augment the soft tissues of the midface. Site 5 targeted the region of the maxillary ligament to lessen the nasolabial folds, and site 6 targeted the mandibular ligament to reduce the marionette line. Conclusions: This site-specific injection technique targeting the true ligaments may lead to increased efficiency and accuracy of face rejuvenation and exert a lifting effect. Level of Evidence: 4: